Garlic Extract-Mediated SPIONs-Incorporated Nanohydrogel for Enhanced Wound Healing Potential - Parmanik, Ankita; Bose, Anindya; Panigrahi, Lipsa Leena; Sahoo, Rudra Narayan; Nayak, Amit Kumar (Current Drug Delivery, 2025)
<span class=
Keywords: wound healing